2011 IEEE Nuclear Science Symposium Conference Record 2011
DOI: 10.1109/nssmic.2011.6152666
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic performance characteristics of the IQ●SPECT system

Abstract: The IQ-SPECT system was introduced by Siemens in 2010 to significantly improve the efficiency of myocardial perfusion imaging (MPI) using conventional, large field-of-view (FOV) SPECT and SPECT-CT systems. With IQ-SPECT, it is possible to perform MPI scans in one-fourth the time or using one-fourth the administered dose as compared to a standard protocol using parallel-hole collimators. This improvement is achieved by means of a proprietary multifocal collimator that rotates around the patient in a cardio-cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 1 publication
0
23
0
Order By: Relevance
“…The Symbia camera (Siemens Medical Solutions) is a dualhead Anger camera for which cardiac imaging can be performed either with a low-energy high-resolution collimator (for conventional SPECT) or with a high-sensitivity astigmatic collimator involving a convergent geometry for the image center and parallel holes for the edges (for IQÁSPECT) (6). Conventional SPECT and IQÁSPECT were assessed in the University Hospitals of Nice and Nancy, respectively.…”
Section: G-cameras and Collimation Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Symbia camera (Siemens Medical Solutions) is a dualhead Anger camera for which cardiac imaging can be performed either with a low-energy high-resolution collimator (for conventional SPECT) or with a high-sensitivity astigmatic collimator involving a convergent geometry for the image center and parallel holes for the edges (for IQÁSPECT) (6). Conventional SPECT and IQÁSPECT were assessed in the University Hospitals of Nice and Nancy, respectively.…”
Section: G-cameras and Collimation Systemsmentioning
confidence: 99%
“…These improved systems enhance the sensitivity of count detection and thereby enable recording times or tracer doses to be reduced, a property that has highly favorable consequences on patient comfort and radiation exposure (1-4). This enhancement is based mainly on acquisitions that are heart-centric but obtained with very different technologies: first, for the IQÁSPECT system (Siemens Medical Solutions (5-8)), an Anger camera equipped with collimators convergent on the image center (astigmatic collimators); second, for the DSPECT system (Spectrum Dynamics (9-13)), mobile columns of CZT detectors with wide parallel-hole collimators; and third, for the Discovery NM 530c system (GE Healthcare (14-21)), fixed CZT detectors with multipinhole collimators.The respective performance of these new cameras and collimation systems has been analyzed, but only separately (6,11,14). To our knowledge, there has been no direct headto-head comparison of the performance of the IQÁSPECT, DSPECT, and Discovery NM 530c systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The technologist has to centre the heart as precisely as possible within the sweet spot and the myocardial contrast may often be less than optimal, and thus the effects of mispositioning on the reconstructed image is a concern. This question was addressed by Rajaram et al [1] in a phantom study. They found that final images were significantly affected by different positioning (centring on the base vs. the apex) when they were reconstructed without AC (NAC), while no difference was observed with AC.…”
Section: Technical Featuresmentioning
confidence: 98%
“…SMARTZOOM collimators center on the heart, collecting up to 4 times more counts than LEHR collimators. These collimators magnify the heart while still capturing counts from the entire field of view (4,5). IQ-SPECT's cardiocentric orbit is centered on the heart instead of the gantry's mechanical center, ensuring that the heart is always in the SMARTZOOM collimators' magnification area.…”
mentioning
confidence: 99%